PELAKSANAAN PERLINDUNGAN ANAK TERPADU BERBASIS MASYARAKAT (PATBM) DI KELURAHAN DELIMA TAHUN 2022 - Amanda '; Wazni ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Delima sub-district has the most cases of child violence in Pekanbaru City in 2022. Previously, this sub-district had formed a Community-Based Integrated Child Protection (PATBM) activist group, but acts of violence against children still continued to occur in the area. This research aims to find out how Community-Based Integrated Child Protection (PATBM) will be implemented in Delima Village in 2022 and the inhibiting factors that exist in implementing this policy. The research method used is Qualitative Research with a Descriptive Approach so that it can describe specific things with factual data obtained through interviews and documentation. In this research the author uses George Edward III's theory which suggests that there are 4 indicators that contribute to policy implementation, either directly or indirectly, and each of these indicators influences the other indicators. The results of this research indicate that the implementation of Community-Based Integrated Child Protection (PATBM) in Delima Subdistrict in 2022 is still not running optimally. This is based on the fact that 4 indicators that influence policy implementation have not been achieved, namely communication, such as socialization by the Delima Subdistrict PATBM group, has not been conveyed to all parties involved, especially the community and subdistricts. Resources such as people, budget and facilities are still insufficient to carry out various activities. The disposition of the PATBM of Delima Subdistrict has not shown its seriousness and consistency in implementing policies. Bureaucratic structures that have not been implemented and implemented well, such as socialization and training on the application of SOPs to the various parties involved. The inhibiting factors in implementing PATBM in Delima Subdistrict in 2022 are budget limitations, insufficient human resource capabilities and the absence of coordination with the Subdistrict authorities. Keywords: Policy Implementation, Child Protection